Economic Reform in China : A New Phase - Burton, David; Khor, Hoe.; Kochhar, Kalpana; Tseng, Wanda (Washington, D.C. : International Monetary Fund, 1994)
China's economic performance hs been remarkable since the the reform process began 15 years ago. Notwithstanding the achievements that have been made, a number of serious problems remain. This papers discusses the current reform program and the effors being made to overcome the structural impediments to growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet